Fires, floods and droughts in La Pampa between 1998 and 2018. Analysis from the perspective of Risk and Environmental Disaster (Semiárida, 2020)
In order to know the occurrence of three elements of risk and disaster such as fires, floods and droughts and how these affected La Pampa province between 1998 and 2018, the regulations and the Emergency and/or Agricultural Disaster declarations were analyzed. From the perspective of Risk and Environmental Disaster a total of 68 Emergency Decrees or Agricultural Disaster were issued during a 251 months period, corresponding 28 to droughts, 23 to floods, 16 to fires and 1 to temporal or rainstorm. The largest area of territorial affection was between January and March 2009 due to droughts affecting 14 millions of hectares (96.43% of La Pampa), and the longest period was 68 months (from January 1998 to May 2003) due to floods. It is observed that several urban center are located in the path of each analyzed adversity, which are direct or indirectly affected. As a prevention and a postdisaster action, important infrastructural and regulatory works has been carried out by La Pampa government. Despite that and the specialized vision regarding the agricultural sector, the lack of socialization of the problems and citizen participation in the decision making space persist.
Keywords: Climatic Disaster; adversity in La Pampa; agricultural Emergency in La Pampa